Production of High Frequency Elliptic and Hyperbolic Optic Mirrors - Sedlak, Josef; Muzikant, Dusan; Valasek, Petr; Kouril, Karel (Manufacturing Technology Journal, 2017)
An article provides an overview of production and corresponding issues of one of the most important component of a satellite dish - a high frequency optic mirror that polarizes signals caught by a parabola into a sensor connected to computing (so-called receiver).The article describes an issue of production of high frequency elliptic and hyperbolic optic mirrors forming one of the most important functional components of parabolic satellites designed for ALMA, the biggest and the highest located international astronomic radio telescope in the world. It is situated at a high plateau Chajnantor in Chile, South America.Individual parts of the article are outlined in a sense of a flow of a production technological process including both theoretical and practical analyses of the given issue. A content of the article leads especially to a description and explanation of causes of individual problems during production of elliptic and hyperbolic optic mirrors.
Keywords: Elliptic Optical Mirrors; Hyperbolic Optical Mirrors; High Frequency; Aluminium Alloys; Residual Tension; Chemical Nickel Plating; Galvanic Gilding; Pitting; Radio Telescope ALMA